2001
DOI: 10.1073/pnas.121188598
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus analysis of extracellular putative virulence proteins made by group A Streptococcus: Population genetics, human serologic response, and gene transcription

Abstract: Species of pathogenic microbes are composed of an array of evolutionarily distinct chromosomal genotypes characterized by diversity in gene content and sequence (allelic variation). The occurrence of substantial genetic diversity has hindered progress in developing a comprehensive understanding of the molecular basis of virulence and new therapeutics such as vaccines. To provide new information that bears on these issues, 11 genes encoding extracellular proteins in the human bacterial pathogen group A Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 60 publications
4
52
0
1
Order By: Relevance
“…These data fit with the epidemiological observation of an association between the M serotype and certain pathological conditions in humans and mice (158). On the other hand, a detailed analysis of DNA sequence polymorphism of the set of chromosomal virulence genes studied by Reid et al (192) revealed numerous likely horizontal transfer events between the different M strains, and the authors suspected that generalized phage transduction was responsible for at least some of these gene transfers.…”
Section: Vol 68 2004 Phages and The Evolution Of Bacterial Pathogensupporting
confidence: 81%
See 1 more Smart Citation
“…These data fit with the epidemiological observation of an association between the M serotype and certain pathological conditions in humans and mice (158). On the other hand, a detailed analysis of DNA sequence polymorphism of the set of chromosomal virulence genes studied by Reid et al (192) revealed numerous likely horizontal transfer events between the different M strains, and the authors suspected that generalized phage transduction was responsible for at least some of these gene transfers.…”
Section: Vol 68 2004 Phages and The Evolution Of Bacterial Pathogensupporting
confidence: 81%
“…16A). Sequence analysis of 10 chromosomally encoded fitness factors (extracellular proteins) revealed a striking correlation with the M serotypes of these strains (192). These observations suggest that the S. pyogenes strains (M serotypes) have evolved as distinct pathovars, harboring a specific set of chromosomally encoded fitness factors.…”
Section: Vol 68 2004 Phages and The Evolution Of Bacterial Pathogenmentioning
confidence: 82%
“…1B). To determine whether antibody alone promoted adherence of the bacteria to the A549 cells, strain MGAS5005 was incubated with A549 cells in the presence of affinity-purified rabbit antibody raised against Spy0843, a protein present on the cell surface of strain MGAS5005 (12). The antibody to Spy0843 had no effect on adherence of strain MGAS5005.…”
Section: Antibody To Sic Abrogates the Inhibition Of Adherence Of Sermentioning
confidence: 99%
“…Work in this area, from classic studies (5) to a number of recent discoveries (6), has shown that certain human polymorphisms, some of which are responsible for genetic diseases, are also associated with resistance to common infectious diseases. An equally important but as yet incipient area of research will elucidate how the genetic variation of pathogen populations (7)(8)(9)(10)(11)) is related to genetic structure among their human hosts (12)(13)(14). An initial step in this undertaking is to determine the nature and stability of associations between host and pathogen populations.…”
mentioning
confidence: 99%